(untitled) (AYUSHDHARA, 2024)
Objective: The objective of this review study is to understand the scientific concept behind relation of Ayurveda dietary regimen of mother during entire pregnancy mentioned in Samhitas with growth and development of child in purview of Panchmahabhoot theory. This study can also pave the path for Ayurveda scholars to understand the depth behind the concept of Masanumasik Vriddhi due to special dietary regimen mentioned in Ayurveda Samhitas. Data: Data for this study has been collected mainly from a variety of secondary and tertiary literature sources and online database like PubMed, Scopus available. Review Methods: Keeping the objective of study in mind, various Samhitas along with their commentaries have been reviewed. Various narrative and analytical articles have been referred to critically analyse the undefined concept of dietary regimen of pregnant lady in Ayurveda. Conclusion: The aptness in all Mahabhootas can result in promotion of good health status and its imbalance can result in various ailments. The same is true in case of intrauterine life. Panchmahabhoota can be considered as the basis of genetics in Ayurveda and so if by proper and sequential incorporation of Masanumasik Garbhini Ahara we can prevent as well as cure genetic disorders of fetus. This can improve quality of life of mother, fetus and can prevent the mishappening like miscarriages, abortions, fetal anomalies, post birth defects which are quiet obvious now-a-days.